منهج ابن قيم الجوزية في إعلال الفروق الفقهية - العبدالكريم، عبدالعزيز بن عبدالله بن محمد (عبدالفتاح ادريس, 2017)
This paper-study is a description of the approach of Ibn Al-Qayyim Al Jawziyya (i.e., great Islamic Scholar 1292-1349) in the Reasons and grounds of weakness on the jurisprudential differences between sub-Figh cases where are these are similar in appearances and difference in the ruling. This study is covered his printed books. This type of science is a proof of jurisprudential differences, and the jurisprudential differences are either proven, where the validity of the analogy is not valid, or if the validity of the analogy is correct, and Ibn al-Qayyim has adopted an approach in his books clarifying the Reasons and grounds of weakness on the jurisprudential differences between sub-Figh cases. He either states the denial of the difference, or the ruling of the two sections is stated. The two sections then mention that of a provision that also applies to the other section or makes a compromise between the two provisions by providing for the term settlement, Or to explain the difference without declaring it, or to provide the difference and then to refute it without explicitly stating the denial of the difference, or to provide the weakness of the difference in the form of denial question, and it may provide the views of scientists and be in accordance with the highest difference of them and can be seen through his discussions and aspirations, Among the scholars to deny the difference, or deny the existence of the violator in the denial of the difference.
البحث عبارة عن توصيف علمي لمنهج ابن قيم الجوزية في إعلال وتضعيف الفروق الفقهية بين الفروع المتشابهة في الصورة، والمفترقة في الحكم، من خلال النظر في كتبه المطبوعة، وهذا النوع من العلوم هو قسيم ما يثبت من الفروق الفقهية، والتي ينتفي فيها صحة القياس بين الفروع، فالفروق الفقهية إما مثبتة، ينتفي بها صحة القياس، أو منفية يصح فيها القياس، ولابن القيم في إعلال وتضعيف الفروق منهج انتهجه في كتبه، فهو إما أن ينص على نفي الفرق، أو يورد حكم الفرعين ويثبت أن أحدهما يجري مجرى الآخر أو يورد حكم أحد الفرعين ثم يذكر أن ذلك الحكم ينطبق كذلك على الفرع الآخر أو يسوي بين الحكمين بالنص على عبارة التسوية، أو بإضمار التسوية دون التصريح به، أو يورد الفرق ثم يقوم بتفنيده دون النص صراحة على نفي الفرق، أو يورد الإعلال للفرق بصيغة الاستفهام الإنكاري، كما أنه قد يورد أراء العلماء ويكون موافقا لمن أعل الفرق منهم ويتبين ذلك من خلال مناقشاته وترجيحاته، أو يورد الاتفاق بين العلماء على نفي الفرق، أو ينفي وجود المخالف في نفي الفرق.
Keywords: الفقه الإسلامي -- العلل الفقيه -- الفروق الفقهية -- ابن قيم الجوزية، محمد بن أبي بكر بن أيوب، ت. 751 هـ